1999
DOI: 10.1002/(sici)1096-8628(19990507)84:1<29::aid-ajmg7>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

OEIS complex (omphalocele-exstrophy-imperforate anus-spinal defects) in monozygotic twins

Abstract: The omphalocele-exstrophy-imperforate anus-spinal defects (OEIS) complex is a consistent and recognizable pattern of midline abdominal and pelvic defects. It is rare, affecting 1 in 200,000 to 400,000 pregnancies and is even rarer in twin gestations. This is an autopsy study of OEIS complex in monozygotic twins after pregnancy termination at 20 weeks of gestation. Unremarkable family history but concordance of monozygotic twins for the defects may support the theory that early malformation complexes, e.g., OEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 17 publications
5
49
0
2
Order By: Relevance
“…(, ) and by Lee et al. () summarized autopsy and clinical findings of the OEIS complex with an emphasis on its association with monozygotic twinning. The cited studies by Mastroiacovo noted that large body wall defects may be reported as body stalk anomalies or as a large gastroschisis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(, ) and by Lee et al. () summarized autopsy and clinical findings of the OEIS complex with an emphasis on its association with monozygotic twinning. The cited studies by Mastroiacovo noted that large body wall defects may be reported as body stalk anomalies or as a large gastroschisis.…”
Section: Discussionmentioning
confidence: 99%
“…However, OM as a component of the OEIS complex is associated with twinning and likewise with body stalk anomalies (Bugge 2012). Furthermore, two investigations led by Mastroiacovo et al (1992Mastroiacovo et al ( , 2007 and by Lee et al (1999) summarized autopsy and clinical findings of the OEIS complex with an emphasis on its association with monozygotic twinning. The cited studies by Mastroiacovo noted that large body wall defects may be reported as body stalk anomalies or as a large gastroschisis.…”
Section: Twinning and Female Prevalencementioning
confidence: 99%
“…Thus, maternal serum AFP cannot be used to detect all cases of OEIS, and detailed fetal ultrasound examination remains the best tool with which to detect this condition prenatally. Nevertheless, there have been only a few reports of OEIS diagnosed prenatally based on fetal ultrasound prior to 24 weeks' gestation6–12.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from one case where a maternal aunt of 2 female twins may have been similarly affected [4], all twins had no other affected siblings or family members. There are reports of monozygotic twins concordant for ARM associated with other anomalies, for example, the omphalocele-exstrophy-imperforated anus-spinal defects complex [24]. Apart from one pair of twins concordant for cloacal extrophy [25], we are not aware of any cases reporting concordance of monozygotic twins for an isolated high form of ARM.…”
Section: Discussionmentioning
confidence: 99%